Physical Infrastructure and Economic Performance in Nigeria: A Ridge Regression Analysis - Olaniyi, Oladimeji; Tella, Sheriffdeen Adewale; Onanuga , Abayomi Toyin (Acta Universitatis Danubius. Œconomica, 2023)
In Nigeria, how far the deplorable state of most infrastructural facilities and the state of disrepair affect the growth potentials of the nation is relatively unknown. In view of this, this study investigates the role of infrastructure on economic performance in Nigeria using annual time series data for the period 1990-2019. The study employed Principal Component Analysis to develop an infrastructure index based on six major infrastructure indicators (electricity, telecommunication, rail density, air transport, energy use, and internet penetration) and also utilized the ridge regression estimation technique due to the presence of high multicollinearity among our variables. The study found that infrastructure positively and significantly enhanced economic performance within the period. The study, therefore, recommends the need for the Nigerian government and its agencies to monitor infrastructure spending closely and firmly adhere to due process following the enabling fiscal policy.